Cost Leadership Strategy and Financial Performance: Empirical Evidence from Textile Sector Listed Companies of Pakistan - MUHAMMAD ILYAS; IHTESHAM KHAN; MUHAMMAD NISAR KHAN (Journal of Business & Tourism, 2021)
Organizations concentrate to maximize their value. Therefore, their management are interested in their financial performance. However, management is also interested in minimization of the operational cost. This study examines the cost leadership strategy (CLS) and financial performance in a sample of 132 textile sector firms listed on the Pakistan stock exchange (PSX) during 2008-2016. For analyses used panel data random effect model and the results demonstrate that CLS significantly and positively affect the financial performance of textile sector listed firms of Pakistan. Moreover, control variables such as leverage and dividend payout ratio are significantly affect organizational performance. Finally reveals that study supports the theoretical association of return on assets with independent and control variables. Hence, recommended to follow the CLS to reduce operational costs further and to perform efficiently in the competitive market.